Epistle on the Celebration of Easter (CPG 4612): Transmission and Context of the Slavonic Version in the Late 15th–16th Centuries - Lytvynenko, Viacheslav V. (Studia Ceranea, 2023)
This article examines the Slavonic version of the Epistle on the Celebration of Easter (CPG 4612) by focusing on the issues of transmission and context. It begins with a brief overview of the manuscript tradition and the title of this writing, and then asks what function the epistle carried in medieval Russia where it was copied. The author argues that this function was primarily theological rather than technical (related purely to paschal calculations and calendar). For that purpose, the author does several things. First, he shows that there are good reasons to assume that this epistle was perceived as part of the Athanasian corpus of Orations against the Arians, whose copying was occasioned by the rise of the Judaizers – a group of Russian heretics that denied the most fundamental Orthodox doctrines and exploited the eschatological crisis in 1492 to lead the Christians astray. And second, the author explores the evidence from Iosif Volockij and comes to the conclusion that his Enlightener contains similar theological concerns about the celebration of Easter as we find in the epistle.